2016
DOI: 10.1007/s12350-015-0165-9
|View full text |Cite
|
Sign up to set email alerts
|

The characterization and prognostic significance of right ventricular glucose metabolism in non-ischemic dilated cardiomyopathy

Abstract: Increased RV FDG uptake was associated with RV dysfunction and may be a prognostic predictor of all-cause mortality or heart transplantation in patients with DCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…21 demonstrates that increased RV glucose metabolism is a common feature in patients with idiopathic DCM and confirms the relationship of RV 18 F-FDG uptake with the severity of RV dysfunction already documented in HF. Importantly, this study extends previous results by demonstrating the adverse prognostic role of relative increase of glucose metabolism in the RV as compared with the LV underlying the importance of biventricular functional and metabolic changes in these patients.…”
Section: Rv Myocardial Blood Flow and Metabolism In Dcmsupporting
confidence: 80%
“…21 demonstrates that increased RV glucose metabolism is a common feature in patients with idiopathic DCM and confirms the relationship of RV 18 F-FDG uptake with the severity of RV dysfunction already documented in HF. Importantly, this study extends previous results by demonstrating the adverse prognostic role of relative increase of glucose metabolism in the RV as compared with the LV underlying the importance of biventricular functional and metabolic changes in these patients.…”
Section: Rv Myocardial Blood Flow and Metabolism In Dcmsupporting
confidence: 80%
“…Additional data demonstrated that the metabolic switch is still preserved 6–8 weeks after TAC in mice (Kolwicz et al, 2012 ; Pereira et al, 2013 , 2014 ), and this has been also validated in other animal models of pressure overload or volume overload or HF in rats, rabbits and dogs (Taegtmeyer and Overturf, 1988 ; Allard et al, 1994 ; Christe and Rodgers, 1994 ; Christian et al, 1998 ; Labinskyy et al, 2007 ). Another study, this time in patients suffering from non-ischemic DCM, right ventricle glucose uptake had been monitored by PET imaging (using the radioactive isotope [ 18 F] fluodeoxyglucose) (Wang L. et al, 2016 ). Conclusions of these experiments demonstrated a correlation between increased right ventricle glucose uptake and dysfunction (Wang L. et al, 2016 ).…”
Section: Metabolic Adaptations Beyond Good and Evil In Cardiac Diseamentioning
confidence: 99%
“…Another study, this time in patients suffering from non-ischemic DCM, right ventricle glucose uptake had been monitored by PET imaging (using the radioactive isotope [ 18 F] fluodeoxyglucose) (Wang L. et al, 2016 ). Conclusions of these experiments demonstrated a correlation between increased right ventricle glucose uptake and dysfunction (Wang L. et al, 2016 ). In addition, a recent paper established the metabolomics profile of non-ischemic HF in patients (Mueller-Hennessen et al, 2017 ).…”
Section: Metabolic Adaptations Beyond Good and Evil In Cardiac Diseamentioning
confidence: 99%
“…24 Increased RV FDG uptake is associated with RV dysfunction (Figure 3) and may be a prognostic predictor of all-cause mortality or heart transplantation in patients with dilated cardiomyopathy. 25 There is a significant correlation between RVEF and RV FDG uptake; in patients with a cRVSUV (correct RV standard uptake value) [ 7.01, heart transplantation is more frequent. Furthermore, there is a good correlation between RV dysfunction, RV FDG uptake, and severe pulmonary hypertension (mean pulmonary artery pressure C 40 c Figure 1.…”
mentioning
confidence: 99%
“…mmHg, or an RV systolic pressure C 50 mmHg); and severe pulmonary hypertension has a poor prognosis. 24,25 Thus, RV performance in patients of pulmonary hypertension requires optimal assessment; and RV dyssynchrony measured by phase analysis of FDG-PET is significantly related to RV dysfunction. 26 Figure 2.…”
mentioning
confidence: 99%